Upaya Perlindungan Hukum terhadap Dampak Pembangunan Ibu Kota Nusantara terhadap Kepemilikan Tanah Masyarakat Lokal - Wanda Putri Dzakiah; M.Sudirman; Benny Djaja (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
The development of the Nusantara Capital City (IKN) in East Kalimantan presents significant legal challenges regarding local communities' land ownership. Although regulations such as Law Number 3 of 2022 on the National Capital, Law Number 2 of 2012 on Land Procurement for Public Interest Development, and Law Number 5 of 1960 on Basic Agrarian Principles provide legal protection mechanisms, the reality on the ground indicates various obstacles in implementing these laws. Therefore, this study aims to analyze the legal protection available for land ownership held by local communities in the development of IKN. Additionally, it seeks to identify challenges related to the implementation of the prevailing legal framework. An empirical juridical approach is employed to examine legislative provisions and field realities, including conflicts arising in the land acquisition process. The findings reveal that legal protection remains hindered by a lack of transparency, weak access to justice for local communities, and uncertainty in the compensation mechanism. Consequently, improving transparency, strengthening regulations, and ensuring active community involvement in every stage of land procurement are crucial to prevent the development of IKN from compromising the rights of local communities.